Puberdade em tourinhos da raça Nelore avaliada pelo perímetro escrotal, características seminais e endócrinas - Fabrizia Portes Cury Lima (2009)
This work was carried out in order to characterize by zootechnical, seminal and hormonal parameters, aspects related to puberty and sexual precocity of genetically selected Nelore bulls. Twenty four Nelore bulls (8 animals/group) were divided according to the scrotal circunference (SC) at 12 months of age: Group 1 (SC> 22.8 cm); Group 2 (SC between 21.6 and 22.6 cm) and Group 3 (SC between 20.1 and 21.2 cm). The animals were kept under the same environmental and management conditions since birth in paddocks and received silage corn added to concentrate in the trough. G1 animals, with bigger SC at 12 months, reached puberty earlier. At this time these animals were younger and presented less weight when compared to G2 and G3 animals. The testicular growth pattern was maintained among the groups because the G1 animals presented higher SC measures at both moments (12 months of age and puberty). The G1 had the lowest weaning weight, lower age and weight at puberty and increased SC measures compared to G2 and G3. Difference was found in growth rate among the three groups. Group 1, considered the earliest, had higher weight gain until 15 months of age. The testosterone concentration (T) at puberty has a positive correlation with the SC at puberty, because the G1 had higher SC and higher T concentration and the G2 animals had lower SC and lower T concentration. The testosterone plasm values at 12, 14, 16 and 18 months of age were of 3.0, 3.2, 4.3 and 7.1 ng/mL, respectively. The cortisol evaluation indicated increased concentration of this hormone when the animals were 14 months of age. This moment is related to challenging and stress situations to animals. The seminal assessment helped on the sexual precocity evaluation. The semen physical aspects had a progressive increase in quality after animals reached sexual maturity and sperm morphology aspects showed continuous decline during the observations. The results indicated that the period of greatest increase in scrotal circunference of animals occurred between 12 and 14 months of age, suggesting that puberty in these animals is very early and that seminal and endocrine parameters are related to SC and they can be used a trait for selection of early bulls